2021
DOI: 10.1108/apjba-03-2021-0123
|View full text |Cite
|
Sign up to set email alerts
|

Examining the impact of relational benefits on continuance intention of PBS services: mediating roles of user satisfaction and engagement

Abstract: PurposeThe purpose of this study is to examine the dimensionality of relational benefits in public bike sharing (PBS) and explore the mediating role of user satisfaction and engagement on the linkage between relational benefits and continuance intention.Design/methodology/approachThis study used a mixed method approach. Data were collected using convenience sampling technique from 411 users of PBS in Bhubaneswar, India. In the first part of the study, in-depth interviews were conducted to identify a set of rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 75 publications
1
6
0
Order By: Relevance
“…The more engaged the consumer is with mobile payment, the more likely it is that they will continue to use it in the long term. This is in accordance with previous research (Pattnaik and Shukla, 2021; Qing and Haiying, 2021). Hence, as a result of the COVID-19 pandemic, consumers have continued to use mobile payments instead of traditional ones.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The more engaged the consumer is with mobile payment, the more likely it is that they will continue to use it in the long term. This is in accordance with previous research (Pattnaik and Shukla, 2021; Qing and Haiying, 2021). Hence, as a result of the COVID-19 pandemic, consumers have continued to use mobile payments instead of traditional ones.…”
Section: Discussionsupporting
confidence: 94%
“…The influence of attitude on consumer engagement has been validated for mobile payments (Alhassan et al, 2020;Raman and Aashish, 2021). Additionally, prior research has confirmed the positive relationship between user engagement and continuance intention (Kim et al, 2019;Pattnaik and Shukla, 2021;Qing and Haiying, 2021). We therefore postulated:…”
Section: Hypothesis Developmentmentioning
confidence: 93%
“…see: Hudaefi and Beik, 2021; Hudaefi et al , 2022b) and complement evidence of quantitative analysis (e.g. see: Hudaefi and Noordin, 2019; Pattnaik and Shukla, 2021).…”
Section: Methodsmentioning
confidence: 68%
“…Service providers (hereafter, providers) generally follow various relationship-building strategies such as communications, preferential treatment and service personalization (Odekerken-Schr€ oder et al, 2003;Mishra and Vaithianathan, 2015) for maintaining relationships with existing customers. It has similarly been argued in the literature that customers who benefit from providers' relational strategies show greater intentions of relationship continuation (Pattnaik and Shukla, 2021).…”
Section: Relationship Marketing Orientationmentioning
confidence: 93%